Rygor natychmiastowej wykonalności a zasada równości stron: [Immediately enforceable of judgments and the principle equality of the parties] (Studia Prawnicze / The Legal Studies, 2015)
W postępowaniu cywilnym obowiązującą zasadą jest, że przymusowemu wykonaniu podlegają jedynie orzeczenia prawomocne. Od zasady tej ustawodawca przewidział jednak wyjątki. Mianowicie, zgodnie z art. 388 § 1 k.p.c. w razie wniesienia skargi kasacyjnej, gdyby na skutek wykonania orzeczenia stronie mogłaby być wyrządzona niepowetowana szkoda, sąd drugiej instancji może wstrzymać wykonanie zaskarżonego orzeczenia do czasu ukończenia postępowania kasacyjnego lub uzależnić wykonanie tego orzeczenia – w razie oddalenia apelacji także orzeczenia sądu pierwszej instancji – od złożenia przez powoda stosownego zabezpieczenia. I odwrotnie, w pewnych sytuacjach prawodawca przewidział możliwość uzyskania przez wierzyciela pełnego zaspokojenia jeszcze przed uprawomocnieniem się orzeczenia, dopuszczając jego natychmiastową wykonalność. Wykonalność ta może wynikać z mocy ustawy, bądź orzeczenia sądowego. Author of the article describes the problems related to the legitimacy and enforceability of judgments which are enforceable later. The obligation to enforcement of the judgment is also stemmed from the rule of law. This principle implies an order to take over in legal authorities and institutions of the measures directly aimed to enforce the provisions of the final judgment by the courts. Namely, in the case of the cassation appeal, if as a result of enforcement side could be caused irreparable damage, the court of second instance may suspend implementation of the contested judgment until the completion of the appeal or make the execution of that judgment – in the event of dismissal of the appeal as court of fi rst instance – from submission through the plaintiff reasonable protection. Conversely, in some situations, the legislator has provided the possibility for a judgment creditor even before the execution of the decree, allowing its immediate implementation. The feasibility of this may be due by law or judicial decision.